The Effect of Using Contextual Guessing Technique on Students’ Reading Comprehension at Tenth-Grade of SMKN 1 Kepenuhan Hulu - Bulan, Sri; Niati, Batdal; Kasyulita, Evi (Science, Technology and Education Care (STEDCA), 2025)
This research aimed to determine whether using the Contextual Guessing Technique significantly affects students’ reading comprehension in the tenth grade of SMKN 1 Kepenuhan Hulu. The data analysis technique this researcher uses is statistical analysis, namely descriptive analysis. The data gained was taken from the students in the tenth grade of SMKN 1 Kepenuhan Hulu. The instrument used in collecting the data was a reading test. The population of the research consisted of three classes. The researcher used a sample of two classes, which became the experimental class and the control class. The study found that contextual guessing significantly affected students’ reading comprehension. It can be seen that the result of the hypothesis testing was 0.000. It was lower than α =0.05. And the result t-value = 9.524 and t-table = 2.064. It is t-value > t- t-table, meaning that Ho was rejected and Ha was accepted. The use of CGT had a significant effect on students' reading comprehension. The students' reading comprehension improved through the Contextual Guessing Technique. Using this technique, students do not spend their time searching for the meaning of words using a dictionary